Barang Rongsokan dan Peluang Bisnis Berbasis Ekonomi Sirkular Di Sulawesi Selatan: Tinjauan Literatur Kualitatif - Nurhaedar, Nurhaedar; Azwar Wijaya Syam; Muhammad Dakhri; Muh. Yasin Noor W.K; Tahalua, Imran (Al-Buhuts, 2025)
This study aims to analyze the potential and challenges of scrap-based business practices within the framework of the circular economy in South Sulawesi Province. The method employed is a qualitative approach using a systematic literature review. Data sources were obtained from relevant national and international academic publications, policy documents, and institutional reports related to waste management, the informal sector, and circular economy implementation in Indonesia, particularly in South Sulawesi. The literature analyzed spans the past five years (2020–2025) and was selected based on thematic relevance, source credibility, and its contribution to theoretical and policy development. The findings indicate that the most dominant types of scrap materials within the informal supply chain include ferrous metals, PET and HDPE plastics, and electronic waste. Informal actors such as waste pickers, local collectors, and micro-enterprises play a central role in the collection and distribution of these materials. However, they face various structural barriers, including limited access to technology, finance, legal recognition, and persistent social stigma. The study also finds that the lack of institutional synergy and spatial mapping hinders the logistical efficiency of local recycling systems. This research highlights the need for integrating affirmative policies, enhancing environmental literacy, and fostering community-based social innovations as foundational strategies to build an inclusive, resilient, and sustainable circular economy ecosystem in South Sulawesi.